Numerical evaluation of the damping solvent extraction method in the frequency domain. - Basu, Ushnish (Earthquake engineering & structural dynamics.)
The damping solvent extraction method for the analysis of unbounded visco-elastic media is evaluated numerically in the frequency domain in order to investigate the influence of the computational parameters-domain size, amount of artificial damping and mesh density on the accuracy of results. An analytical estimate of this influence is presented, and specific questions regarding the influence of the parameters on the results are answered using the analytical estimate and numerical results for two classical problems : the rigid strip and rigid disc footings on a visco-elastic half space with constant hysteretic material damping. As the domain size in increased, the results become more accurate only at lower frequencies, but are essentially unaffected at higher frequencies. Choosing the domain size to ensure that the static stiffness is computed accurately leads to an unnecessarily large domain for analysis at higher frequencies. The results improve by increasing artificial damping but at a slower rate as the total (material plus artificial) damping ratio gets closer to 0.866. However, the results do not deteriorate significantly for the larger amounts of artificial damping, suggesting that 0.6 is appropriate; a larger value is not likely to influence the accuracy of results. Presented results do not support the earlier suggestion that similar accuracy can be achieved by a large bounded domain with small damping or by a small domain with larger damping.